2008
DOI: 10.2225/vol11/issue4-fulltext-9
|View full text |Cite
|
Sign up to set email alerts
|

Anaerobic membrane bioreactors: Are membranes really necessary?

Abstract: Membranes themselves represent a significant cost for the full scale application of anaerobic membrane bioreactors (AnMBR). The possibility of operating an AnMBR with a self-forming dynamic membrane generated by the substances present in the reactor liquor would translate into an important saving. A selfforming dynamic membrane only requires a support material over which a cake layer is formed, which determines the rejection properties of the system. The present research studies the application of self-forming… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 1 publication
0
13
0
2
Order By: Relevance
“…Dynamic membranes appear to be a promising approach for solving problems associated with high membrane cost, rapid membrane fouling and low membrane flux as such membranes exhibit low cost with high permeation at low transmembrane pressure [112]. Moreover, dynamic membranes can also improve the effluent quality [112][113][114].…”
Section: Dynamic and Self-assembly Membranesmentioning
confidence: 99%
See 2 more Smart Citations
“…Dynamic membranes appear to be a promising approach for solving problems associated with high membrane cost, rapid membrane fouling and low membrane flux as such membranes exhibit low cost with high permeation at low transmembrane pressure [112]. Moreover, dynamic membranes can also improve the effluent quality [112][113][114].…”
Section: Dynamic and Self-assembly Membranesmentioning
confidence: 99%
“…The performance of dynamic membrane, therefore, depends upon various characteristics and process conditions used, with resulting differences in cake density and cake characteristics, playing a key role in the membrane's permeability. Creation of dynamic membranes, however, differs both between AnMBRs and aerobic MBR system [109,113].…”
Section: Dynamic and Self-assembly Membranesmentioning
confidence: 99%
See 1 more Smart Citation
“…[4][5][6][7][8]. Meshes of different porosity ranging from 10 to 500 µm have been reported in literature as a suitable support material for developing DMs [7][8][9][10]. The filtration mechanism of DMs is quite different to conventional MF/UF membranes in a way that, after the formation of DM layer, the filtration resistance is exclusively caused by the cake layer [7].…”
Section: Introductionmentioning
confidence: 99%
“…They found that the best effluent quality and sludge retention efficiency were achieved with a pore size of 100 μm. On the other hand, Jeison et al () showed that pore sizes of over 60–70 μm were not suitable for cake layer accumulation. Thus, smaller pore sizes should be selected for anaerobic dynamic membrane applications.…”
Section: Introductionmentioning
confidence: 99%